Q01 SIRT 1 mediated modulation of circulating cytokines in huntington's disease- pharmacodynamics results from phase 1B study of selisistat—A SIRT 1 inhibitor. (29th August 2012) - Haider, S; Andre, R; Farmer, R; Süssmuth, S; Frost, C; Bjorkqvist, M; Westerberg, G; Landwehrmeyer, B; Tabrizi, SJ; ,
Abstract : Background: Evidence suggests simultaneous dysfunction of CNS and peripheral inflammatory pathways in Huntington's disease (HD). A pattern of pro-inflammatory cytokine elevation has been observed in plasma in HD, with IL-6 significantly elevated in a group of subjects predicted to be, on average, 16 years from disease, with a parallel post-mortem cytokine expression profile seen in HD striatum. Furthermore, LPS stimulation of HD monocytes reveals an inherent hyper-reactivity that is similar to that seen in microglia, suggesting a cell-autonomous effect of mutant huntingtin in peripheral myeloid cells as well as in the CNS. Sirtuins, which are deacetylating enzymes, have been implicated as potential targets in ageing, metabolism and neurodegeneration. Selisistat, a member of the sirtuin deacetylase family and an inhibitor of SirT1 (Silencing information regulator T1), has a novel mode of action that may be pathologically relevant for HD. A Phase 1B study encompassing six EU sites (Germany, Poland and the UK) was carried out in 55 early-stage HD patients over 14 days at two dose levels (10 and 100 mg OD), with a randomised, double-blind, placebo-controlled, parallel group design. Aim: To determine if the innate immune system is a potential target for Selisistat. Methods: Cytokine assays were carried out using the MesoScale Discovery (MSD) multiplex platform, as per the manufacturer's recommendations, and analysed on a SECTOR 2400 instrument. The cytokines of interest included IL-1b, IL-6, IL-8 and TNF-α. The operator was blinded to the disease state of each sample during processing and statistical analysis was performed independently. Results and Conclusions: Here we will present comparative analysis of the plasma cytokine profile of Huntington's disease patients at four time points, screening, baseline, day 14 and day 28, in each of the three treatment arms of the study.